O-23 Bearing witness at a time of crisis: methodological reflections on interviewing young adults with life-limiting or life-threatening conditions in inclusive research. (19th November 2022) - Earle, Sarah; Blackburn, Maddie; Chambers, Lizzie; Downing, Julia; Flemming, Kate; Hale, Jamie; Marston, Hannah; O'Dell, Lindsay; Sinason, Valerie; Watts, Lucy; Whitney, Sally
Abstract : Background: There is a strong imperative to include patients and the public in palliative care research, but the literature is dominated by discussion of the methodological, practical and ethical difficulties (van der Steen, Bloomer, & Martins Pereira, 2022. Palliat Med. 36:4). The concerns raised are complex and varied but they include sensitivities surrounding talk on death and dying, the presumed vulnerability of people at end-of-life, research burden, the role of gatekeepers, and the perceived potential of doing harm (Crowhurst, 2013. Int J Soc Res Methodol. 16:463; Blum, Inauen, Binswanger et al., 2015. Prog Palliat Care. 23:75; Turner & Almack, 2017. Int J Soc Res Methodol. 20:485). Aims: The study investigated the unintended consequences of pandemic control measures during the first wave of the Coronavirus pandemic in the UK. Methods: We draw on an inclusive qualitative research study informed by constructivist grounded theory methodology (Charmaz, 2006) on the experiences of young adults (aged 18-40) with life-limiting or life-shortening conditions. The project was led by a multi-disciplinary team of researchers including co-researchers with lived experience. Twenty-eight young adults participated in in-depth online interviews and were asked to reflect on their involvement in the study; this paper explores some of the methodological implications of this. Results: Findings highlight the opportunities for participants of being involved in palliative care research, even at a time of crisis, when the possibility of doing harm might reasonably be heightened. Four themes were identified that address this including the opportunity to: (1) help others and influence change, (2) talk about private, seldom-discussed issues, (3) receive therapeutic benefit and, (4) reciprocity and exchange. Conclusions: Our study shows that within inclusive qualitative research, participants are not the passive, vulnerable actors that they are assumed to be. In contrast to the view that participating in research is distressing and harmful, this study shows that it can give individuals the opportunity to share hidden, often painful stories in a context that can be experienced as positive and enriching. This project has explored the experiences of an under-researched group and considered the importance of bearing witness to their experiences through research.